HOMILADOR AYOLLAR HISSIY-EMOTSIONAL SOHASI DIAGNOSTIKASI - Kalandarova, M.B. (SCIENCE and SOCIETY, 2019)
The article analyzes the factors affecting the emotional environment of pregnant women. There have been presented the results of a psychological study aimed at identifying the relationships of pregnant women.